2022
DOI: 10.1021/acsanm.1c03522
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Photoluminescence for Optoelectronic Applications via Precision Fabrication of Quantum Dot/Au Nanoparticle Hybrid Assemblies

Abstract: The distance-dependent interaction of an emitter with a plasmonic nanoparticle or surface forms the basis for the application of such systems within optoelectronics. Semiconductor quantum dots (QDs) are robust emitters due to their photostability. A key challenge is the formation of well-defined assemblies containing QDs and plasmonic nanoparticles in high purity. Here, we present the translation of DNA-based self-assembly to assemble metal and semiconductor nanocrystals into hybrid structures. The high purity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…One of the most prominent factors to control the fluorescence enhancement is the distance between the plasmonic metal and the emitting semiconductor components. Demonstration of the distance effect on emission enhancement in semiconductor–metal nanoparticles was reported for CdSe/ZnS core/shell nanoparticles deposited on Au colloids with a defined polyelectrolyte spacer allowing controlled distance between the semiconductor nanoparticles and the gold films . Maximum enhancement by a factor of 5 was achieved for a 9-layer spacer (∼11 nm) due to a local enhanced electromagnetic field around the metal nanostructures (Figure A).…”
Section: Synergetic Properties Of Hnps: Whole Is Greater Than the Sum...mentioning
confidence: 97%
See 2 more Smart Citations
“…One of the most prominent factors to control the fluorescence enhancement is the distance between the plasmonic metal and the emitting semiconductor components. Demonstration of the distance effect on emission enhancement in semiconductor–metal nanoparticles was reported for CdSe/ZnS core/shell nanoparticles deposited on Au colloids with a defined polyelectrolyte spacer allowing controlled distance between the semiconductor nanoparticles and the gold films . Maximum enhancement by a factor of 5 was achieved for a 9-layer spacer (∼11 nm) due to a local enhanced electromagnetic field around the metal nanostructures (Figure A).…”
Section: Synergetic Properties Of Hnps: Whole Is Greater Than the Sum...mentioning
confidence: 97%
“…Hybrid DNA-based assembly of CdSe/CdS with Au NPs and Au NRs showed a significant fluorescence enhancement of 15−75% depending on the different HNPS architectures in comparison to nonconjugated semiconductor NPs. 167 However, Au rod structures exhibit a greater magnitude of fluorescence enhancement (75% vs 48% for rods and spheres, respectively) due to the strong localization of the near field at the nanorod tips (Figure 19D).…”
Section: Fluorescence Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle assembly is crucial in various application areas, including polymer composites, [ 444 ] thermal management, [ 462 ] microelectronics, [ 102 ] optical devices, [ 463 ] biomedical devices, [ 464 ] magnetic systems, [ 465 ] and biological sensing/detection. [ 466 ] Take the block copolymer‐nanoparticle composite as an example; the distinct morphologies exhibited by block copolymers, such as layered structures, gyroid structures, or hexagonally packed cylinders, offer confinement and organization sites for nanoparticles.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…[31][32][33] Hybrid nanostructures formed by combining plasmonic nanoparticles with excitonic emitters such as semiconductor nanocrystal quantum dots (SQDs) are gaining increasing research attention due to their unprecedented capabilities to manipulate light at the nanoscale. [34][35][36][37][38][39][40][41][42] In 2015, Hartsfield et al experimentally demonstrated the ability of a single SQD with a small scattering cross section to dramatically modify the scattering spectrum of a gold nanosphere kept at nanoscale proximity. [43] The result was stated as highly counter-intuitive as scattering cross sections of the two nanoparticles differed by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%